Engaging students through messaging applications in foreign language learning (Journal of Applied Learning and Teaching, 2023)
This study explores undergraduate students’ experiences and perceptions of group discussions facilitated by eStudentMentors in WhatsApp or Telegram groups in the context of German language learning. eStudentMentors are senior peers who volunteer to support novice language learners. The study was conducted with 159 students enrolled in German Language Level 1 and German Language Level 2 at a university in Singapore. Each of the language classes comprises 15-21 students and are assigned an eStudentMentor to facilitate online learning and discussions in a dedicated WhatsApp or Telegram group. With considerations to information-sharing behaviour, the study examines how receptive students are to online information-sharing in this context. As such, a combined quantitative and qualitative online survey questionnaire was used to collect data, with survey questions examining information-sharing behaviour governed by personality traits and based on the Social Exchange Theory, Social Capital Theory, and theory of instinctive information-sharing behaviour. Overall, 55.97% of the students who completed the survey used the WhatsApp or Telegram groups created by their eStudentMentor to ask or answer questions and share information at least once throughout the semester. In comparison, the other 44.13% were completely inactive in their chat groups. This analysis examined the reasons behind this group of students’ inactivity and found that a major factor for individual inactivity was the overall inactivity of the chats, which makes the active facilitation of the eStudentMentor a crucial element for success. The lack of social bonds appears to be another main reason for inactivity. Additional factors are class size, unfamiliarity with their classmates, fear of judgement, feeling awkward, having negative assumptions, and low commitment levels. The findings counter the Social Exchange Theory (SET) propositions, as the greater benefits of information sharing are overshadowed by the seemingly trivial cost. Yet, these costs in the form of social perceptions and pressures appear to accumulate and collectively outweigh the rationally perceived benefits to the users.